Konceptual′nì v zasadii pravovogo regulûvannâ spoživčogo kredituvannâ v Ukraїnì - Lepeh, Svìtlana (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2013)
The article addresses the research of principles of consumer crediting legal regulation in Ukraine. The author stresses, that conceptual attitudes concerning the improvement of legislation on consumer crediting are as follows: specification of peculiarities of these relations contractual regulation; balancing of legislative guaranties of the interests of these social relations participants. The author makes her own propositions as to the improvement of current civil legislation of Ukraine.
Keywords: Ukraina; kredyt konsumencki; regulacje prawne